Anatomical Characteristics of Patent Ductus Arteriosus and Choice of Transcatheter Occluder Devices - Rafique, Saima; Imtiaz, Sana; Akhtar, Khurram; Mehmood, Amjad; Ara, Andaleeb; Wahab, Abdul; Sadiq, Abubakar; Kamran, Javeria (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the anatomical characteristics of Patent Ductus Arteriosus, choice of transcatheter occluder device and outcomes of Patent Ductus Arteriosus device closure.Study Design: Analytical Cross-sectional study.Place and Duration of Study: Paediatric Cardiology Department, Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi Pakistan, from Jan-July 2023.Methodology: A total of n=90 patients regardless of age and gender presenting with Patent Ductus Arteriosus, who underwent device closure were enrolled in this study by universal sampling. Data of the patients was collected on pre-designed proforma. Pearson's Chi-square test was applied to find association of morphological type of ductus and the weight of patient with the type of device used. p-value < 0.05 was considered as statistically significant.Results: Among n=90 patients, 56(62.2%) were females and 34(37.8%) were males with median age of 1(IQR=0.6-4.25) years who underwent transcatheter device closure. The most common ductus types treated were Krichenko type-A 70(76.7%). Devices used were VSD device 15(16.7%), ADO-II 6(6.7%) and ADO-I device (conventional duct occluder) 69(76.7%). Median fluoroscopy time was 8.40(7.2-12.07) minutes. Statistically significant relationships were observed between Krichenko classification of Patent Ductus Arteriosus, weight of patient and type of device used to occlude the Patent Ductus Arteriosus (p